Benedykt Hesse as a representative of Cracow academic community of the first half of 15th century - Wojtczak, Hanna (Folia Philosophica, 2012)
Re-establishing of the Cracow University in 1400 led to forming the Cracow School of philosophy being unique in its practicalism, tolerance, probabilism, concordism, eclecticism, Buridanism in philosophy of nature, ethics and anthropology, and focus on natural sciences, as well as in highlighting the methodological distinction of the orders of faith and knowledge, philosophy and theology. All of these characteristics might be found in the work of Benedykt Hesse, one of the main representants of Cracow academic community of the first half of 15th century.